TIDAK DIPENUHINYA UPAH PEKERJA YANG DIRUMAHKAN PADA MASA PANDEMI COVID-19 SEBAGAI PERBUATAN MELAWAN HUKUM - Dimitria Pawestri Kusumadewi (2023)
The Covid-19 pandemic was designated as a non-natural disaster through Presidential Decree (Keppres) of the Republic of Indonesia Number 12 of 2020 concerning Stipulation of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 (Covid-19). This Presidential Decree forms the basis. This policy is good for the health sector, but has implications for decreasing company productivity and income. The decline in productivity and income is the reason for the company to make the decision to lay off its workers. This decision is to prevent termination of employment (PHK), because layoffs will have implications for the provision of severance pay and other workers' rights as stipulated in Law Number 13 of 2003 concerning Manpower jo. Law Number 11 of 2020 concerning Job Creation. This research examines 2 problems, namely: what are the elements of unlawful acts committed by employers in laying off workers during the Covid-19 Pandemic and how is the implementation of fulfilling the rights of laid-off workers during the Covid-19 Pandemic? This study aims to examine the elements of unlawful acts and the implementation of fulfilling the rights of workers who were laid off during the Covid-19 pandemic. The conclusion of the research shows that the company's actions to lay off workers are contrary to the Labor Law which legally only regulates layoffs. The consequence of layoffs is that the company provides severance pay and the rights of sick workers as stipulated by law. Companies that laid off workers during the Covid-19 pandemic are required to provide workers with wages and rights as long as there are no permanent layoffs.